Efek Kurkumin terhadap Aktivitas Enzim Glutation Peroksidase Mitokondria Hati Tikus - Syamsudin Syamsudin; Suyatna FD; Ganiswarna S; Sadikin M (Fakultas Farmasi Universitas Pancasila, 2004)
This study was conducted to prove the hypothesis that Curcumin could prevent the oxidative damage of rat liver mitochondria induced by t-butylhydroperoxide (t-BHP). The induction of 400 uMt-BHP reduced Gluthatione Peroxidase (GPx) activity from (0.29+0.03) to (0.04+0.01) umol/min/mg protein. Instillation of Curcumin of 1000 uM could elevate GPx activity to (0.16+0.002) umol/min/mg protein.